Crystallographic texture and precipitation control via double austenitization in high-performance tool steel - Hamza Sofiane Meddas; Muftah Zorgani; Majid Heidari; Mousa Javidani; Tom Levasseur; Mohammad Jahazi (Materials & Design, 2025)
In the present work, the toughness and wear resistance of AISI A8 cold work high-strength tool steel were improved through the design of a specific double austenitization and tempering heat treatment. The treatment resulted in 80 % improvement in impact toughness and 10 % improvement in wear resistance. A combination of high-resolution dilatometry and scanning electron microscopy, including phase compositional and crystallographic analysis, was used to identify the microstructural changes. The findings were analyzed in terms of the influence of the proposed heat treatment on the refinement of the as-quenched martensite substructure and the fraction of high-angle grain boundaries (V1/V2, V1/V3 and V1/V6) variant pairs and the fraction of low-angle grain boundaries (V1/V4) pairs. Notably, block width analysis revealed that in the double austenitization treatment, block width appeared insensitive to prior austenite grain size variations. Additionally, the kinetics of the M23C6 secondary carbides precipitation during isothermal tempering at 520 °C was investigated and modeled. Results demonstrate that the redistribution of carbon in solid solution is the critical microstructural parameter influencing the variant selection and the homogenous precipitation of spherical carbides. The underlying micro-mechanisms responsible for such improvement were identified and their contributions documented and quantified.